Compare: 69/39 A, page 73 and BG A8/386, BG A8/423 and BG A8/427 for the original photo on which this painting was based
Compare: 69/39 A, page 73 and BG A8/386, BG A8/423 and BG A8/427 for the original photo on which this painting was based.